HLA mismatches that are identical for the antigen recognition domain are less immunogenic. (June 2018) - Roelen, Dave; Vaal, Yvonne; Vierra-Green, Cynthia; Waldvogel, Stephanie; Spellman, Stephen; Claas, Frans; Oudshoorn, Machteld
Abstract For hematopoietic stem cell transplantation (HCT) HLA 10/10 (HLA-A, B, C, DRB1, DQB1) matched donors are optimal, but are not available for all patients. The identification of permissive/non-immunogenic mismatches may improve the outcome of HLA mismatched transplants. We hypothesize that HLA alleles identical within the antigen recognition domain (ARD), but mismatched outside the peptide binding groove or α-helices are often permissive mismatches. We evaluated the functional impact of non-ARD mismatches by performing in vitro functional T cell assays. Cytotoxic T Lymphocyte precursor assays were performed for 23 HLA class I mismatches and 96% (22 out of 23) were negative. Mixed lymphocyte reaction assays were conducted on 10 HLA class II mismatches and all were negative. However, 4 out of 10 combinations were positive in the Elispot and all involved one direction: a DRB1*14:01/DRB3*02:01 responder against a DRB1*14:54/DRB3*02:02 stimulator. These positive responses were confirmed by Primed Lymphocyte Testing and the DRB1* mismatch seemed to be responsible for the response. In conclusion, HLA mismatches with amino-acid differences outside the ARD are not very immunogenic. However, in some cases weak T cell reactivity in vitro can be observed. The impact of these responses on clinical outcome of HCT remains to be established.